Computation of Degree-Based Topological Descriptors Using M-Polynomial for Coronoid Systems. (21st April 2022) - Julietraja, K.; Venugopal, P.
Abstract: This paper aims to compute the degree(valence)-based molecular descriptors for coronoid polycyclic aromatic hydrocarbons. The myriad types of coronoids have potential far-reaching applications in evolving fields such as nanotechnology and synthetic organic chemistry due to their superaromaticity and other extraordinary geometric and electronic properties. The degree-based connectivity descriptors, like the Randić, the sum-connectivity, the first and second Zagreb indices, and its co-indices have a strong correlation with the total π-electron energy and other properties which are significant for the synthesis of coronoid polycyclic aromatic compounds. In this article, the various degree(valence)-based topological descriptors are computed using the M-polynomial for coronoid structures with cavities that vary depending on their topology, which will benefit future researchers in exploring and synthesizing new coronoid structures. The analytical expressions for recently developed molecular descriptors are also derived. The degree-based indices have not been studied earlier for coronoid structures, which contributes substantial weightage to this research work. Additionally, the computed degree-based indices are compared both graphically and numerically.